2016
DOI: 10.3389/fpls.2016.00450
|View full text |Cite
|
Sign up to set email alerts
|

EcoTILLING-Based Association Mapping Efficiently Delineates Functionally Relevant Natural Allelic Variants of Candidate Genes Governing Agronomic Traits in Chickpea

Abstract: The large-scale mining and high-throughput genotyping of novel gene-based allelic variants in natural mapping population are essential for association mapping to identify functionally relevant molecular tags governing useful agronomic traits in chickpea. The present study employs an alternative time-saving, non-laborious and economical pool-based EcoTILLING approach coupled with agarose gel detection assay to discover 1133 novel SNP allelic variants from diverse coding and regulatory sequence components of 113… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…Further, we sought to identify genetic variations among the small‐ and large‐seeded cultivars that might be responsible for differential gene expression and determine seed weight/size in chickpea. For this analysis, we integrated the known QTLs (based on genomic coordinates) and candidate genes (based on gene identifiers) associated with seed size/weight reported in previous studies (Kujur et al ., , ; Saxena et al ., ; Bajaj et al ., , ; Verma et al ., ; Singh et al ., ) with our differential gene expression results. A total of 34 genes, including those located in the QTLs, genes associated with seed weight/size, involved in cell cycle/cell division, endoreduplication and seed storage protein accumulation and/or showing higher transcript abundance in JGK 3 at S3 and/or S5 stages as compared with Himchana 1, were identified (Figure a; Dataset 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, we sought to identify genetic variations among the small‐ and large‐seeded cultivars that might be responsible for differential gene expression and determine seed weight/size in chickpea. For this analysis, we integrated the known QTLs (based on genomic coordinates) and candidate genes (based on gene identifiers) associated with seed size/weight reported in previous studies (Kujur et al ., , ; Saxena et al ., ; Bajaj et al ., , ; Verma et al ., ; Singh et al ., ) with our differential gene expression results. A total of 34 genes, including those located in the QTLs, genes associated with seed weight/size, involved in cell cycle/cell division, endoreduplication and seed storage protein accumulation and/or showing higher transcript abundance in JGK 3 at S3 and/or S5 stages as compared with Himchana 1, were identified (Figure a; Dataset 4).…”
Section: Resultsmentioning
confidence: 99%
“…Quite a few studies have identified QTLs and/or candidate genes associated with seed size/weight in chickpea using different biparental populations or diverse germplasm via various approaches (Kujur et al ., , ; Saxena et al ., ; Verma et al ., ; Bajaj et al ., , ; Singh et al ., ). In most of these studies, large genomic regions harboring several genes have been identified as QTLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renewed efforts could mirror, to an extent, what the dedicated international centre did back during the 70 s and 80 s, by creating a panel of common accessions for phenotypic screening, and for development of populations with shared molecular information. Such steps are critical also in the development of mapping populations, linkage mapping, and Genome Wide Association Studies (GWAS) for trait discovery, as shown in soybean (Li et al 2018), chickpea (Bajaj et al 2016;Saeed and Darvishzadeh 2017), mung bean (Noble et al 2018), and common bean (Tock et al 2017). This would allow us also to combine phenotypic and genetic data across different environments and assess the degree of adaptability and plasticity of winged bean.…”
Section: Future Directionsmentioning
confidence: 99%
“…Ecotilling, a variant of Tilling (Targeting Induced Local Lesions IN Genomes) method, allows high-throughput analyses of natural genetic diversity in populations [12][13][14]. In this technique, a single-strand specific endonuclease extracted from celery (CEL I) is used to cleave DNA where there are mismatched bases in the DNA heteroduplexes of PCR products.…”
Section: Introductionmentioning
confidence: 99%